Economics confronts the economy - Klein, Philip A. (Cheltenham, UK ; North Hampton, MA : Edward Elgar, 2005)
In this book the author Phil Klein, in a low key but deeply reasoned text, critiques economic theory for its misrepresentations of the economy and other shortcomings. In particular, Klein provides a critique of how mainstream economists - creating a corpus of doctrines that seem "quantitative, precise, logical, elegant, rigorous, and beautiful" - have made more of Adam Smith's "invisible hand" than did Smith himself.
Includes bibliographical references.
rpm 22/10/13
Loans
Keywords: Economics -- Study and teaching; Economic history